Bacteriophages of Helicobacter pylori - Muñoz, Angela B.; Stepanian, Johanna; Trespalacios, Alba Alicia; Vale, Filipa F. (Frontiers in Microbiology, 2020)
The bacterium Helicobacter pylori colonize the stomach in approximately half of the world’s population. Infection with this bacterium is associated with gastritis, peptic ulcer, adenocarcinoma, and gastric mucosa-associated lymphoid tissue lymphoma. Besides being a pathogen with worldwide prevalence, H. pylori show increasingly high antibiotic resistance rates, making the development of new therapeutic strategies against this bacterium challenging. Furthermore, H. pylori is a genetically diverse bacterium, which may be influenced by the presence of mobile genomic elements, including prophages. In this review, we analyze these issues and summarize various reports and findings related to phages and H. pylori, discussing the relationship between the presence of these elements and the genomic diversity, virulence, and fitness of this bacterium. We also analyze the state of the knowledge on the potential utility of bacteriophages as a therapeutic strategy for H. pylori.